Basis Teologi Normatif Pendidikan Islam Multikultural Dalam Alquran Dan Hadits - Suardi Kandjai (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
This article examines the normative theological foundations of multicultural Islamic education derived from the Qur’an and Hadith as a basis for developing an inclusive and equitable educational system. The study aims to analyze the concept of normative theology in multicultural education and to identify multicultural values from the perspectives of the Qur’an, Hadith, and their relevance to civic life. The method employed is library research using a descriptive-analytical approach to various classical and contemporary literatures. The findings indicate that normative theology in Islam substantively encompasses multicultural values such as tolerance (tasāmuh), justice (‘adl), equality (musāwah), and brotherhood (ukhuwwah). The Qur’an emphasizes that diversity is a divine decree (sunnatullah) that must be respected and rejects all forms of coercion in religion. Meanwhile, the Hadith of the Prophet Muhammad (peace be upon him) reinforces these principles through teachings of universal compassion, respect for fellow human beings, and the prohibition of discrimination. In the context of civic life, these values imply the importance of policies that uphold social justice, protect minority groups, and strengthen interreligious and intercultural dialogue. Thus, Islamic education based on normative multicultural theology plays a strategic role in shaping students who are moderate, tolerant, and capable of contributing to a pluralistic society. These findings underscore the urgency of integrating multicultural values into the Islamic education system as a response to global challenges and contemporary social dynamics.